2017
DOI: 10.1016/j.arth.2017.04.063
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Caseload and Usage in Determining Outcomes of Unicompartmental Knee Arthroplasty: A Meta-Analysis

Abstract: Title: The interaction of caseload and usage in determining outcomes of unicompartmental 1 knee arthroplasty: A meta-analysis 2 Abstract 3Background: Outcomes following UKA are variable and influenced by surgical caseload 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 92 publications
3
68
0
2
Order By: Relevance
“…For any new orthopaedic implant, favourable results would be expected from developing centres, and whilst it might be rational to assume that similar outcomes will not be achieved by the wider surgical community, our series forms part of a growing number of independent reports of good results and favourable revision rates [6, 7, 9, 10]. There are also reports from other units with less success [11–14], but the main contrast comes from concerns raised primarily by registry data [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For any new orthopaedic implant, favourable results would be expected from developing centres, and whilst it might be rational to assume that similar outcomes will not be achieved by the wider surgical community, our series forms part of a growing number of independent reports of good results and favourable revision rates [6, 7, 9, 10]. There are also reports from other units with less success [11–14], but the main contrast comes from concerns raised primarily by registry data [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports from other units with less success [11–14], but the main contrast comes from concerns raised primarily by registry data [30]. Inevitably the performance of an implant is dependent on the technique used to implant it, and studies have demonstrated the effect of a significant learning curve for UKA [3134] with some authors advocating minimum numbers to be undertaken in order to maintain competence [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was expected, higher rates were found in younger patients. The youngest modelled patient age was 55, and patients of this age were found to have a lifetime revision risk of 15% (CI [12][13][14][15][16][17][18][19]. This reduced to a lifetime risk of 4% (CI 3-5) for those of 85 years of age at operation.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 14% of US UKA surgeries were performed with robotic assistance as of 2012 and this rate is expected to increase [11]. Studies have also observed an association between high-volume centres and better outcomes, in particular revision rates [15][16][17]. e capital costs of robotic assistance mean that a crude comparison of procedural costs of traditional instrumentation versus robotic-assisted UKA would favour the traditional procedure [12].…”
Section: Introductionmentioning
confidence: 99%